How to make better use of our Central Provident Fund (CPF) system to support retirement life. - Tan, Yanzhen. (2009)
With aging population, more and more elderly in Singapore do not have adequate funds for retirement. This could bring about social and economic issues that might hinder the nation’s growth. Hence, there is a need to evaluate our fully self-funded pension plan in Singapore which comes in the form of Central Provident Fund (CPF), and to discuss the different initiatives undertaken by the Government. The objective of this paper is to investigate ways to help retirees in Singapore better utilise their CPF savings in order to retire more comfortably. To achieve this, we compared returns from CPF LIFE with private annuities and investment-linked products. Besides, we explored ways to allocate one’s investment portfolio under CPFIS to maximise his retirement fund. We also discussed how housing may be used as an alternative to sustain one’s retirement life. All in all, we should not depend solely on the Government to secure our retirement life. Instead, it is every individual’s responsibility to plan ahead for an adequate retirement.